THE SYMBOLS OF THE MOON AND SUN IN ENGLISH AND UZBEK LITERATURE - Akhmadalieva Gulmira Marufjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the emergence of the term "symbolism" in Uzbek, Russian and English language, and the meanings of the symbolic expressions "Moon" and "Sun" in literature.